Projecting the past : ancient Rome, cinema, and history - Wyke, Maria (New York : Routledge, 1997)
- Ancient Rome, cinema and history##- Projecting ancient Rome##- Spartacus: testing the strength of the body politic##- Cleopatra: spectacles of seduction and conquest##- Nero: spectacles of persecution and excess##- Pompeii: purging the sins of the city##- A farewell to antiquity.
Filmography: p. 212-216.
Includes bibliographical references (p. 217-229) and index.
boek